THE ECONOMICS OF AI-DRIVEN PRODUCTIVITY: ARE TRADITIONAL GROWTH MODELS OBSOLETE? - Loso Judijanto; Novira Fazri Nanda; Baskoro Ajie (Adisam Publisher, 2025)
This study aims to analyze the relevance of traditional economic growth models in the context of artificial intelligence-driven productivity gains. The rapid development of AI has triggered significant changes in the structure of production, distribution, and consumption, raising questions about whether classical theoretical frameworks such as the Solow growth model, endogenous theory, and human capital-based models are still capable of explaining modern growth dynamics. Using a literature review, this study examines recent empirical and theoretical findings related to AI's contribution to productivity, its impact on labor markets, and its implications for income distribution. The analysis shows that AI introduces a new factor of production,